Biomass/biochar carbon materials for CO2 capture and sequestration by cyclic adsorption processes: a review and prospects for future directions - Karimi, Mohsen (2022)
The persistent enhancement of greenhouse gases in the atmosphere originated from anthropogenic activities, especially CO2, resulted in several serious global challenges. In this way, employing biomass, biochar, etc., as a low-cost precursor for CO2 adsorbent is promising not only in the view of hydrophobic character and abundant resources, but also is an illustrious strategy for solid wastes management as a consequence of the exponential population expansion. Herein, key concepts on adsorption technology, waste management, and different activation techniques on raw carbons materials have firstly been discussed. Afterwards, almost all accomplished studies on cyclic adsorption processes e.g. PSA, TSA, VSA, etc., which employed biomass/biochar as a source of adsorbents have been extensively reviewed, that gives a precise knowledge for large scale application of these materials. Furthermore, in the last part of this work, biomass/biochar adsorbent based samples, which have already been studied for CO2 capture, but till now, they have not been evaluated at the bench/pilot scale by cyclic adsorption process, are introduced for future directions. Also for the reader’s of this work, key concepts of each section have been summarized in the form of simple figures and tables that will help to identify clearly the prominent accomplished works till now.